Strong non‐growing season N uptake by deciduous trees in a temperate forest: A 15N isotopic experiment. (28th August 2021) - Ma, Linna; Xu, Xiaofeng; Zhang, Chaoxue; Lv, Yixia; Liu, Guofang; Zhang, Qibing; Feng, Jinchao; Wang, Renzhong
Abstract: Nitrogen (N) is a critical element for vegetation growth and subsequent carbon (C) and nutrient cycling in terrestrial ecosystems. Plant N uptake, the only pathway for plants to directly obtain N from soils, is a bottleneck process for ecosystem C and N cycling. Ecological theories predict that deciduous trees remain dormant and do not take up N during winters as no growth occurs during this season. In this study, we adopted a 15 N isotopic experiment to trace N processes throughout the non‐growing season in a temperate forest in northern China. The 15 N‐labelled inorganic N ( NH 4 + and NO 3 ‐ ) and 13 C 15 N‐labelled organic N (glycine and tyrosine; equivalent to 150 mg 15 N/m 2 ) were applied to soils at mid‐fall, and the 15 N recovery in various components of dominant evergreen and deciduous species was analysed. We found that soil N transformation remained active in the winter and microbial N immobilization reached its peak in late winter. Surprisingly, deciduous species maintained a high N uptake that was comparable with the evergreen species throughout the non‐growing season. Perennial herbs did not take up N until the next spring. All plant species acquired inorganic N and simple amino acids, while only the tree species utilized complex amino acids. Throughout the non‐growing season, evergreen and deciduous trees showed higher uptake rates for NH 4 + and glycine than NO 3 ‐ and tyrosine, while deciduous shrubs and herbs showed a stronger preference for NO 3 ‐ over other N forms. Synthesis . The finding that deciduous trees have strong N uptake in the non‐growing season challenges the conventional viewpoint that deciduous trees remain dormant during non‐growing seasons. This mechanism might supplement the algorithm in the model representation of N‐limited temperate forest ecosystems. Abstract : The finding that deciduous trees have strong N uptake in the non‐growing season challenges the conventional viewpoint that deciduous trees remain dormant during non‐growing seasons. This mechanism might supplement the algorithm in the model representation of N‐limited temperate forest ecosystems.